MERANCANG TES GRAMMAR ENGLISH FOR SPESIFIC PURPOSES (ESP) UNTUK MAHASISWA KESEHATAN MASYARAKAT DI INSTITUT KESEHATAN DELI HUSADA DELI TUA - Sulastri Ginting; Tedty Rohaya Tinambunan (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2021)
The study is designing English Grammar Assessment for public health students at Institut Kesehatan Deli Husada Deli Tua. The objectives of the study are : (1) Investigate English grammar assessment which meet to the public health students’ needs at Institut Kesehatan Deli Husada Deli Tua. (2) Design English grammar assessment through ACA. The method of the stufy is qualitative research. The writer evaluates the English grammar assessment on students’ material book which is used by them on teaching learning process. Based on the result shows that the assessment is too general for health students. The assessments are not suitable for helath field. It brings the writer to interview students to find out students’ needs on learnign English, especially on grammar. Then the writer design the new grammar assessment which are appropriate to Health Public Students and also validate it. This thesis result found the following: (1)The ESP theory should be considered for deciding grammar assessment to students of public health. Health Students need grammar assessments which are related to health field. (2) New English grammar are designed through ACA to find out the appropriate assessment for Health Students. ACA uses authentic materials as an approach in deciding appropriate assessment which is given to the students. The aunthentic materials are required to them to face the real situation in workplace later. The teacher gives the English grammar assessment, future planning. The assessment about future planing which is talking about health field. The result of questionnaire shows that the new English grammar assessment are relevant to the Health Students in Institut Kesehatan Deli Husada Deli Tua.